PHYLOGENETIC CHARACTERIZATION OF PSYCHROPHILIC ° BACTERIA ISOLATED FROM DEEP-SEA WATER OF THE NANKAI TROUGH - Ocky Karna Radjasa; Kumiko Kita-Tsukamotoz; Hidetoshi Urakawal; Kouichi Ohwadai (JOURNAL OF COASTAL DEVELOPMENT, 2001)
A screening among 4